A (des)motivação na aprendizagem de língua inglesa dos acadêmicos de Letras da Universidade Federal do Amapá - PEREIRA, Márcia Helena Matias (UNIFAP – Universidade Federal do Amapá, 2022)
Motivation is a prominent issue in the educational area due to its importance to the teaching/learning process. It is through motivation that the students start and finish their studies, facing the difficulties that appear during this path, mainly when it comes to college education, where the barriers increase and highly challenge the undergraduate students in their university trajectory. Thus, the aim of this monograph is to investigate the motivational aspect of the undergraduate students of the Portuguese/English Language Education Course of the Federal University of Amapá– UNIFAP. In addition, this work investigates the possible causes of their demotivation, shows the kinds of motivation that exist and are applied to the teaching area, the current studies about this topic, and outlines a profile of the English language learner of this referred institution towards the motivational area. Therefore, bibliographic and field researches were carried out, and this last one is a qualitative approach research, that uses methods and techniques of the Ethnographic Research, allowing the use of the of the data collection instruments obtained from the students of the Portuguese/English Language Education Course of UNIFAP as well as from the coordination office of this referred course. These procedures were utilized in order to show an overview of the reality of the undergraduate students regarding their English Language learning, bringing along important contributions, not only to the professors but also to the students of this public university teaching institution.